STUDY ON FLOOD CONTROL INFRASTRUCTURE IN SINGKAWANG - (NIM : 15007073); Pembimbing : Ir. Iwan Kridasantausa, M.Sc., Ph.D., HENDRI
Floods occur almost every year in Singkawang. Floods are the result of runoff in rivers and inadequate drainage capacity. The purpose of this study was to plan a flood control system so the city can operate with optimal and indirectly affect economic activities in the city and surrounding Singkawang. The scope of discussion include : the identification problem of flooding and its causes, analysis and distribution of rainfall over the period of plan for 10,25, and 50 years, to determine Snyder’s Synthetic Unit Hydrograph and Nakayasu’s Synthetic Unit Hydrograph, analysis of the rate erosion, analysis of tidal, flood control systems planning, modeling and simulation of existing conditions and plans. The data required to perform the analysis include : topographic maps, river network system maps, land use maps, watershed maps, postal of rain maps, flood area maps, at least 10 years of rainfall data, the measurement of cross section of the river, and tidal measurement data. Results from the overall analysis done of the alternative 2. Proposed alternative flood control system 2 is the creation of embankments along the River Selakau, normalization and redimensi Singkawang River, River Sedau, Kulor Canal, and the installation of door controllers in meeting Kulor Canal and Garam River, River Setapuk Kecil, River Raso, River Rasau, River Setapuk Besar, River Semelagi Besar, River Semelagi Kecil, and River Daun. Alternative 2 share discharge on the drainage canal Kulor to the Garam River and Setapuk Kecil River before entering the River Selakau.